Diversity and distribution of polyporales in Peninsular Malaysia - Mohamad Hasnul Bolhassan; Noorlidah Abdullah; Vikineswary Sabaratnam; Hattori Tsutomu; Sumaiyah Abdullah; Noraswati Mohd. Noor Rashid; Md. Yusoff Musa (Universiti Kebangsaan Malaysia, 2012)
Macrofungi of the order Polyporales are among the most important wood decomposers and caused economic losses by decaying the wood in standing trees, logs and in sawn timber. Diversity and distribution of Polyporales in Peninsular Malaysia was investigated by collecting basidiocarps from trunks, branches, exposed roots and soil from six states (Johor, Kedah, Kelantan, Negeri Sembilan, Pahang and Selangor) in Peninsular Malaysia and Federal Territory Kuala Lumpur. This study showed that the diversity of Polyporales were less diverse than previously reported. The study identified 60 species from five families; Fomitopsidaceae, Ganodermataceae, Meruliaceae, Meripilaceae, and Polyporaceae. The common species of Polyporales collected were Fomitopsis feei, Amauroderma subrugosum, Ganoderma australe, Earliella scabrosa, Lentinus squarrosulus, Microporus xanthopus, Pycnoporus sanguineus and Trametes menziesii.